2024
DOI: 10.1186/s12888-024-05627-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of empagliflozin as adjunctive therapy to citalopram in major depressive disorder: a randomized double-blind, placebo-controlled clinical trial

Atefeh Zandifar,
Maryam Panahi,
Rahim Badrfam
et al.

Abstract: Background Major depressive disorder is one of the most common psychiatric disorders, which is associated with a high disease burden. Current treatments using antidepressants have limitations, so using medication with neuromodulating and anti-inflammatory properties alongside them could be helpful. In a clinical trial, we studied the effectiveness of empagliflozin, a blood sugar-lowering drug, as an adjunctive therapy to reduce the severity of depression symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Population‐based studies suggest that SGLT2 inhibitors are associated with a decreased risk of dementia and depression (Liebers et al., 2023 ; Wu et al., 2023 ). Preclinical experiments have shown that these medications can improve brain energetics (Pawlos et al., 2021 ), and a recent randomized controlled trial demonstrated improved mood outcomes with the selective SGLT2 inhibitor empagliflozin in combination with citalopram (Zandifar et al., 2024 ). These findings suggest that SGLT2 inhibitors may have a broader therapeutic potential beyond their glycemic control effects.…”
Section: Introductionmentioning
confidence: 99%
“…Population‐based studies suggest that SGLT2 inhibitors are associated with a decreased risk of dementia and depression (Liebers et al., 2023 ; Wu et al., 2023 ). Preclinical experiments have shown that these medications can improve brain energetics (Pawlos et al., 2021 ), and a recent randomized controlled trial demonstrated improved mood outcomes with the selective SGLT2 inhibitor empagliflozin in combination with citalopram (Zandifar et al., 2024 ). These findings suggest that SGLT2 inhibitors may have a broader therapeutic potential beyond their glycemic control effects.…”
Section: Introductionmentioning
confidence: 99%